2002
DOI: 10.1021/bc025573a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Novel Histidine-Tagged Tat-Peptide Complexes Dual-Labeled with 99mTc-Tricarbonyl and Fluorescein for Scintigraphy and Fluorescence Microscopy

Abstract: To enable concurrent whole body scintigraphy and direct imaging of subcellular localization of permeation peptides, dual-labeled Tat-peptides useful for both radiometric analysis and fluorescence microscopy are desired for molecular imaging applications. Thus, novel dual-labeled D-Tat-peptides comprising Tat-basic domain (hgrkkrrqrrrgc), C-terminus conjugated with fluorescein-5-maleimide (FM) and N-terminus chelated with [(99m)Tc(CO)(3)] via histidine coordination, were synthesized and characterized. In human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
2
7

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 44 publications
6
80
2
7
Order By: Relevance
“…For this probe, a modified Tat peptide sequence has been used as the targeting moiety. A number of studies using Tat-derived peptides have demonstrated transport and intracellular delivery of molecular imaging as well as therapeutic agents into various cell types and tissues (19,36,(39)(40)(41)(42). In addition, we have previously shown the utility of this peptide for enhancing the intracellular accumulation of a conjugated fluorophore in relevant target cells, in this case, RGCs (20).…”
Section: Discussionmentioning
confidence: 99%
“…For this probe, a modified Tat peptide sequence has been used as the targeting moiety. A number of studies using Tat-derived peptides have demonstrated transport and intracellular delivery of molecular imaging as well as therapeutic agents into various cell types and tissues (19,36,(39)(40)(41)(42). In addition, we have previously shown the utility of this peptide for enhancing the intracellular accumulation of a conjugated fluorophore in relevant target cells, in this case, RGCs (20).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there is no endotoxin contamination in TAT-BH4 peptide. It is important to note that both of these compounds should be delivered to most cells in the body, but penetration across the blood brain barrier may be limited (33,35,36). Although lymphocytes are a primary target of sepsis-induced apoptosis, the gastrointestinal epithelial cells also undergo a large acceleration in apoptosis during sepsis (3,14).…”
Section: Discussionmentioning
confidence: 99%
“…To prepare the fluorescent labeled TAT-BH4, (d) Ac-C (FM) RKKRR-Orn-RRR-␤-A-(l)-SNRELVVDFLSYKLSQKGYS-COOH, an N terminus cysteine, was included in the initial solid state peptide synthesis of the peptide and, following HPLC purification, the peptide was thiol conjugated to fluorescein maleimide (1.2 equivalent; Molecular Probes) at ambient temperature in 50% dimethylformamide/water for 2 h. Quantitative yields were analyzed by C 18 reverse-phase HPLC. For labeling, cells were suspended for 30 min in modified Earl's balanced salt solution containing 1 M fluorescently labeled TAT-BH4 (33). Control cells were treated identically, except no labeled TAT-BH4 was added.…”
Section: Laser-scanning Confocal Microscopy Of Tat-bh4-treated Human mentioning
confidence: 99%
“…In a previous study, however, no PTD mediated transduction in brain was observed, [46] possibly because beta-gal was chemically conjugated to PTD instead of recombinant fusion protein. Similarly, another study also failed to deliver PTD- 99 Tc to the brain [76]. Since PTD is conjugated to Tc or beta-gal, this might have resulted in structural modifications in the PTD and hence no transduction was observed.…”
Section: Potential Of Ptd-fusion Protein Transduction In Vivomentioning
confidence: 99%